Critical Review of Electro-Mechanical Door Locking System and Proposal towards Development of Innovative Super Energy Saving Door Locking System - Sivarao, Subramonian; Taufik; Yuhazri, Yaakob; Haeryip , Sihombing (2012)
This article presents a critical review of electromechanical door locking system. Electromagnetic lock is currently widely used in the market. But it has common disadvantages such as low break-in force, and requires continuous power supply in order to maintain the locked state, higher power consumption and limited life of the back-up battery. Power supply failure may drain the back-up battery due to the necessity of providing continuous supply of electrical energy to maintain the locked state of the door. Hence the electromechanical takes the role as a competitor. To challenge the magnetic type lock, solenoid now become preferable instrument for automatic door locking as they can save energy up to 50 percent or more. Market demand shows that the fail secure and fail safe modes are now priorities. Fail safe mode of a lock describes a mode wherein the door can be opened by the lock doorknob when power to the lock is turned off or malfunction. Conversely, the fail secure mode describes a mode wherein the door cannot be opened by the doorknob when power to the lock is off or malfunction. Ten types of electromechanical door lock with recent development were analyzed and revealed here. On top of that, a new innovative solution is proposed to be the best of all above in term of power saving, performance, quality and efficiency.